Photosynthesis and enzyme activities regulating starch biosynthesis in different varieties of cassava (Manihot esculenta crantz) - Geethu Krishnan P R (Department of Plant Biotechnology, College of Agriculture, 2016)
The present study on Photosynthesis and enzyme activity regulating starch biosynthesis in different varieties of cassava (Manihot esculenta Crantz) was conducted during the period of 2015-2016 in the Division of Crop Production, ICAR-CTCRI, Thiruvananthapuram. The objective of the study was to study the relation between photosynthesis, leaf area, crop duration and enzymes activities regulating starch biosynthesis in four varieties of cassava (Manihotesculenta Crantz) and to determine limiting factor(s) for low starch content of tubers in low starch varieties. Four varieties selected for the study are viz., SreeVijaya, SreeAthulya, H165, H226. SreeAthulya, a triploid long duration variety had the maximum starch and sucrose content whereas H165, a short duration variety, had the minimum starch content. The different parameters such as morphological, biochemical, enzyme activity, and photosynthetic activity were recorded / assayed for four cassava varieties. Morphological parameters are number of leaves, leaf area, leaf area index and tuber yield. Maximum noumber of leaves and leaf area was observed in the variety SreeVijaya. Photosynthetic activity was observed maximum in the variety SreeVijaya. The minimum number of leaves and leaf area were observed in the varieties H226 and H165. The maximum tuber yield was observed in the variety H226 and minimum tuber yield was observed in the variety H165. Biochemical parameters like sucrose content and starch content were maximum in in the variety SreeAthulya and minimum in the variety H165. The enzymes activities involved in starch biosynthesis assayed in the present study are viz., AGPase, SPS, SS, SuSy and invertase. SreeAthulya had the highest AGPase activity and SuSy activity and high tuber yield. SreeVijaya had the highest SPS activity. H165 had the lowest tuber yield due to decrease in leaf area, sucrose and starch content, photosynthetic activity, lowest enzymatic activities of SuSy, SS. Generally the photosynthetic activity the activities of